Akibat Hukum Dilibatkannya Penduduk Sipil Dalam Konflik Bersenjata Antara Milisi Dan Tentara Pemerintah - Ervin Septory; Johanis Steny Franco Peilouw; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The relationship between people or groups of people incorporated in a different nationality or state of the community can be an indirect or official relationship undertaken by state officials that hold negotiations on behalf of the state and inaugurated the approval achieved in such an official inter-state agreement.Purposes of the Research: to know and understand the legal consequences of the civilian population involvement in armed conflict between militias and government soldiers.Methods of the Research: Based on the problems studied, this researcher uses a type of "Normative Juridical" research, namely research on legal rules, norms, and principles related to the problem being studiedResults of the Research: The results of this study explain that the regulation of the civilian population in the armed conflict is the most important in the case between militia and government army according to international law and international humanitarian law, armed conflict is a conflict to be enforced in human rights (human rights). As the form of legal efforts on the involvement of civilians in the armed conflict between militia and government army clearly raises the terms of the rules that apply to the main factor because the case occurred in the Ethopia state involving civilians in armed conflicts is an action that must be attempted to effectively in the congestion to address the problems or cases that occur in Ethopia as well as the armed conflicts have a huge impact of losses for the two parties who are bathed.